2021
DOI: 10.1039/d1ra01603b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of (2R,3R)-2-(3,4-dihydroxyphenyl)chroman-3-yl-3,4,5-trihydroxy benzoate as multiple inhibitors of SARS-CoV-2 targets; a systematic molecular modelling approach

Abstract: Structure-based insilico-guided screening of potential polytargeting anti-COVID phytochemical: gallocatechin gallate analogue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Finally, the hydrogen receptors were merged into the target receptor molecule using the Discovery Studio 4.1 client. 20 Prepared protein was validated through a Ramachandran plot ( Fig. 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the hydrogen receptors were merged into the target receptor molecule using the Discovery Studio 4.1 client. 20 Prepared protein was validated through a Ramachandran plot ( Fig. 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Before and aer protein reduction, the potential energy, van der Waals energy, electrostatic energy, and RMS gradient of the complex were measured, and the pH used was 7.4. Finally, the hydrogen receptors were merged into the target receptor molecule using the Discovery 20 Prepared protein was validated through a Ramachandran plot (Fig. 2).…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…The obtained data suggested that tannic acid was a potential inhibitor of the targeted enzyme, as it was found to form a thermodynamically stable complex with Mpro. Cinnamtannin-B is another naturally occurring tannin that has been reported as a top hit against SARS-CoV-2 Mpro [ 137 ]. Cinnamtannin-B is derived from the cinnamon plant ( Cinnamomum zeylanicum ) and can only be isolated from a limited number of plants such as Linderae umbellatae and bay laurel ( Laurus nobilis ) [ 138 ].…”
Section: Phytochemicals As a Reservoir To Search For Sars-cov-2 Mpro ...mentioning
confidence: 99%
“…Molecular dynamics (MD) simulations are widely used to investigate spatial and temporal fluctuations of biomolecules. MD simulations of processes such as protein–drug interactions and folding/unfolding of proteins in the explicit solvent require micro- to millisecond length simulations to provide the chemical and biological inferences that researchers commonly probe. The number of iterations or time steps can range from tens to hundreds of millions.…”
Section: Introductionmentioning
confidence: 99%